Reading Practices, Postcolonial Literature, and Cultural Mediation in the Classroom - Berezan, David Harris Kenneth (Alberta Journal of Educational Research, 2014)
Ingrid Johnston and Jyoti Mangat’s compact and comprehensive text, Reading Practices, Postcolonial Literature, and Cultural Mediation in the Classroom, provides readers, educators, researchers, policy makers, and educational administrators invaluable insights into how difference in race, ethnicity, tradition, language, gender, class and power can be negotiated through the integration of postcolonial discourse and literature into English Language Arts classrooms.